2009
DOI: 10.1007/s11191-008-9150-x
|View full text |Cite
|
Sign up to set email alerts
|

Developing Greek Primary School Students’ Critical Thinking through an Approach of Teaching Science which Incorporates Aspects of History of Science

Abstract: In this paper,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…This contrasts the claim of the Minsitry of Education (2010) or a notion frequently reproduced by newspapers eg (Lakasas, 2010), based on Greek students' performance in PISA (OECD, 2010) that the Greek educational system teaches memorization only and not critical thinking. It is in line, however, with other studies that have shown that critical thinking can be, and is being cultivated in Greek schools (Malamitsa, Kasoutas, & Kokkotas, 2009). Of course, the fact that Greek 14 year old children have developed some analytical thinking does not mean that it cannot be further developed.…”
Section: Discussionsupporting
confidence: 87%
“…This contrasts the claim of the Minsitry of Education (2010) or a notion frequently reproduced by newspapers eg (Lakasas, 2010), based on Greek students' performance in PISA (OECD, 2010) that the Greek educational system teaches memorization only and not critical thinking. It is in line, however, with other studies that have shown that critical thinking can be, and is being cultivated in Greek schools (Malamitsa, Kasoutas, & Kokkotas, 2009). Of course, the fact that Greek 14 year old children have developed some analytical thinking does not mean that it cannot be further developed.…”
Section: Discussionsupporting
confidence: 87%
“…"The TER was developed out of the CCTST" (Facione, 2001, p. 14) a tool which has been used in scientific studies involving over 7900 students from 50 colleges and universities (Facione et al, 2002, p. 5). The sample of the standardization research consisted of 350 persons, including primary school students, secondary education students and undergraduate students (Malamitsa, Kasoutas, & Kokkotas, 2008, 2009a. In the present research, TER was translated into Greek and standardized.…”
Section: Theoretical Assumptions Concerning the Definition And Assessmentioning
confidence: 99%
“…In this way students could understand how science works, they could develop the Critical Thinking skills needed to critically analyze texts and interpret graphs and charts (vignettes, short historical extracts of scientists' biographies, historical experiments, historical photos, pictures, drawings, graphs/ charts etc.). The incorporation of History of Science could also motivate students by creating a meaningful learning environment and promote a richer understanding of socioscientific issues through different representations of ideas or data (Kokkotas, 2003;Malamitsa et al, 2009a). Thus, students are facilitated to distinguish between concepts, hypotheses and observations of nature.…”
Section: History Of Sciencementioning
confidence: 99%
See 2 more Smart Citations